The peripheral centre : voices from India's Northeast - Gill, Preeti (New Delhi : Zubaan, 2010)
Contributed articles; chiefly on social conditions of women.
Includes bibliographical references.
Keywords: Women -- India, Northeastern -- Social conditions; Women -- India, Northeastern -- Political activity; India, Northeastern -- Social conditions